The Mathematical Critical Thinking Ability Viewed from Mathematical Disposition in Guided Discovery Learning Model Assisted by GeoGebra Classroom - Wahyu Nur Annisa; Iwan Junaedi; Iqbal Kharisudin (Jurnal Pendidikan Indonesia, 2025)
One factor in students' low critical thinking abilities is the not yet optimal use of learning models and media. The aim of this research is to describe the mathematical critical thinking abilities of class X students in terms of mathematical disposition in the Guided Discovery Learning model assisted by GeoGebra Classroom. This research approach is a qualitative descriptive approach. The population in this study was class X vocational school. The subjects of this research were all students of class X TKR 2. Data collection techniques in this research used test, questionnaire and interview techniques. The selection of research subjects to obtain information through interviews is based on the results of mathematical disposition and mathematical critical thinking abilities. The research results show that Guided Discovery Learning model learning activities assisted by GeoGebra Classroom are effective And in the high mathematical disposition category there are two patterns of mathematical critical thinking ability, in the moderate mathematical disposition category there are four patterns of mathematical critical thinking ability, and in the low mathematical disposition category there are two patterns of mathematical critical thinking ability. The implication of this research is to provide significant insight into the world of education, especially in mathematics learning.